2020
DOI: 10.3390/ijms21124490
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Targets for Glioblastoma Therapy from a Pre-Clinical Approach, Using Nanoformulations

Abstract: Glioblastoma (GBM) is the most aggressive tumor type whose resistance to conventional treatment is mediated, in part, by the angiogenic process. New treatments involving the application of nanoformulations composed of encapsulated drugs coupled to peptide motifs that direct drugs to specific targets triggered in angiogenesis have been developed to reach and modulate different phases of this process. We performed a systematic review with the search criterion (Glioblastoma OR Glioma) AND (Therapy OR Therapeutic)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 112 publications
(980 reference statements)
0
2
0
Order By: Relevance
“…The mechanisms of high neovascularization in GBM have received great attention, including the presence of bizarre vessels and resistance to antiangiogenic therapy, which can be related to different types of angiogenesis [1][2][3][4][5][9][10][11][12][13][14][15][16][17]. It has been suggested that intussusception (intussusceptive microvascular growth) could be a mechanism of compensatory vascular growth occurring in human glioma [18,19], with advantages and inconveniences over classic sprouting angiogenesis [18].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of high neovascularization in GBM have received great attention, including the presence of bizarre vessels and resistance to antiangiogenic therapy, which can be related to different types of angiogenesis [1][2][3][4][5][9][10][11][12][13][14][15][16][17]. It has been suggested that intussusception (intussusceptive microvascular growth) could be a mechanism of compensatory vascular growth occurring in human glioma [18,19], with advantages and inconveniences over classic sprouting angiogenesis [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is now recognized that tumors present alternative mechanisms of vascularization, such as vascular mimicry and the transdifferentiation pathway of tumor cells into endothelial cells. Vascular mimicry represents a model of functional microcirculation generated by tumor cells, lacking endothelial lining, demonstrated by immunohistochemical studies with various endothelial markers, such as CD34 or CD105 [ 19 , 20 , 21 ]. Anti-angiogenic treatments (bevacizumab) and surgical resection followed by temozolomide and radiotherapy have not achieved the expected effect and have not contributed to improving patient survival in the case of glioblastomas [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%